Análisis del intercambio comercial entre Colombia y Francia (2015)
he main goal set out to understand the behavior an d trade relations between Colombia and France, in order to find and analyze p ossible potential opportunities different from those already established; taking in to account two important indicators in the economy of both countries, import s and exports. Once applied the gravity model to trade relations b etween the two countries, we can detect positive and negative variables that hav e affected the exchange and proceeds to do an analysis to increase mutual benef it, identifying potential business opportunities between both countries.